1997
DOI: 10.1128/jcm.35.7.1791-1793.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rhinovirus in sinus brushings of patients with acute community-acquired sinusitis by reverse transcription-PCR

Abstract: Of 20 adults with acute community-acquired sinusitis (ACAS), rhinovirus was detected in specimens from 10 (50%) patients, including maxillary aspirates from 8 (40%) patients and nasal swabs from 9 (45%) patients, by reverse transcription-PCR (RT-PCR). Human coronavirus was detected by RT-PCR in nasal swabs from 3 of 20 patients but in no sinus secretions. These findings suggest that rhinovirus is an important cause of ACAS and that viral invasion of the sinus cavity itself may be a common event during the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 17 publications
1
87
0
4
Order By: Relevance
“…However, evidence of direct viral infection of the maxillary sinus in children is lacking. In adults with acute maxillary sinusitis, a virus can be found in 10% of maxillary secretion samples by viral culture [46] and in 40% by PCR [47].…”
Section: Common Coldsmentioning
confidence: 99%
“…However, evidence of direct viral infection of the maxillary sinus in children is lacking. In adults with acute maxillary sinusitis, a virus can be found in 10% of maxillary secretion samples by viral culture [46] and in 40% by PCR [47].…”
Section: Common Coldsmentioning
confidence: 99%
“…In addition to causing cold symptoms, rhinoviruses have been implicated in the develop-ment of acute sinusitis and in the precipitation of exacerbations of chronic bronchitis and asthma. The virus has been recovered from aspirates obtained by direct puncture of the maxillary sinuses of patients with acute sinusitis (Pitkaranta et al, 1997), and mucosal thickening and/or sinus exudates have been observed in as many as 77% of subjects with acute colds (Turner et al, 1992;Gwaltney et al, 1994). Clinically manifest acute sinusitis is seen in a small (0.5 -5%) proportion of individuals with naturally occurring colds (Wald et al, 1991).…”
Section: Disease Impactmentioning
confidence: 99%
“…Radiographic evidences of sinusitis is frequent during natural or experimental common colds, and in reality the common cold is a viral rhino-sinusitis . Using RT-PCR, viruses, most often rhinoviruses, have been found in up to 40% of sinus samples of adult patients with acute sinusitis (Pitkäranta et al, 1997). Taken together, these studies indicate that human rhinovirus infections are associated with approximately one-half of acute sinusitis in adults and over one-third of otitis media in children.…”
Section: Upper Respiratory Tract Complicationsmentioning
confidence: 85%